Multimodal scaffolding in enhancing EFL writing: Integrating TikTok videos and text outlines - Afrillia Anggreni; Rofiqoh Rofiqoh; Andi Patmasari; Agussatriana Agussatriana; Maf'ulah Maf'ulah; Nirwana Nirwana (English Learning Innovation, 2026)
The rapid growth of digital media in education has placed TikTok as a potential multimodal platform to support writing instruction. This study examined the integration of TikTok videos with narrative text outlines in enhancing EFL students’ writing skills and their perception of this instructional framework. A pre-experimental design involving a one-group pre-test, post-test, and a descriptive survey was employed, involving 32 students of the English Education Program who programmed a Text Type Writing Course. Writing narrative tests and a Likert scale questionnaire were the instruments of this research. The test data were analysed using the non-parametric Wilcoxon, and questionnaire data using descriptive statistical analysis. The statistical results showed that the mean score of the post-test (77.29) was higher than the pre-test (45.22). A Wilcoxon Signed-Rank Test further demonstrated a statistically significant increase in students’ writing skill, which an Asymp. Sig. (2-tailed) is less than the 0.05 significance level, confirming the effectiveness of the instructional intervention. These were also reinforced by survey findings that the instruction framework enabled the students to generate and organise their ideas grammatically, chronologically, and also stimulated their creativity in composing narrative texts. In addition, the survey also revealed that the students experienced positive emotions, increased motivation, and gained meaningful learning experiences. Overall, this pedagogical integration enhanced writing achievement, affective engagement, and simultaneously elevated students’ digital literacy and 21st century skills. This study contributes to a practical and innovative framework for English as a foreign language (EFL) writing pedagogy and develops a theoretical perspective on multimodal literacy.